2009
DOI: 10.4314/eamj.v77i4.46623
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of syphilis in pregnancy in Addis Ababa

Abstract: Objective: To assess the extent of syphilis seropositivity in pregnant women, identify the risk factors associated with it and re-evaluate the need for routine antenatal care screening for syphilis. Design: Prospective cross-sectional study. Setting: Three teaching hospitals of Addis Ababa University Faculty of Medicine, Department of Obstetrics and Gynecology, Addis Ababa, Ethiopia. Subjects: A total of 410 pregnant women attending antenatal care from April 1997 to September 1997 were included in the study. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
9
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 7 publications
10
9
4
Order By: Relevance
“…Therefore, targeted screening is not sufficient, and universal screening would present cost constraints, especially in resource-poor countries. The prevalence rate of syphilis in the present study (0.48%) was very low compared to the rate reported by Kebede et al [18] (2.9%), and the rate reported by Gupta et al, [19] (1.47%). In India, available information indicates that the prevalence of maternal syphilis has remained at around 1.5% between 2003 and 2007 [17].…”
Section: Discussioncontrasting
confidence: 83%
“…Therefore, targeted screening is not sufficient, and universal screening would present cost constraints, especially in resource-poor countries. The prevalence rate of syphilis in the present study (0.48%) was very low compared to the rate reported by Kebede et al [18] (2.9%), and the rate reported by Gupta et al, [19] (1.47%). In India, available information indicates that the prevalence of maternal syphilis has remained at around 1.5% between 2003 and 2007 [17].…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence rate of syphilis in the present study (0.5%) was similar to the rate reported by Mehta et al [4] & very low compared to the rate reported by Kebede et al [5] (2.9%), and the rate reported by Gupta et al, [6] (1.47%). (Table No.2).…”
Section: Discussionsupporting
confidence: 89%
“…Interventions including early ANC, massive screening and prompt treatment with antibiotics have been reported to reduce syphilis attributable-risks [46]. Sero-prevalence of syphilis in the current study was 3.7%, which was consistent with studies conducted in Gondar, 3.7% in Gondar [43], 3% in Madagascar [47], Brazil [31] Bangladesh [48] each, and 2.9% in Addis Ababa, Ethiopia [49].…”
Section: Discussionsupporting
confidence: 88%